Phosphorus Containing Water Dispersible Nanoparticles in Arable Soil. Issue 6 (1st November 2015) - Jiang, Xiaoqian; Bol, Roland; Nischwitz, Volker; Siebers, Nina; Willbold, Sabine; Vereecken, Harry; Amelung, Wulf; Klumpp, Erwin
Abstract : Due to the limited solubility of phosphorus (P) in soil, understanding its binding in fine colloids is vital to better forecast P dynamics and losses in agricultural systems. We hypothesized that water‐dispersible P is present as nanoparticles and that iron (Fe) plays a crucial role for P binding to these nanoparticles. To test this, we isolated water‐dispersible fine colloids (WDFC) from an arable topsoil (Haplic Luvisol, Germany) and assessed colloidal P forms after asymmetric flow field‐flow fractionation coupled with ultraviolet and an inductively coupled plasma mass spectrometer, with and without removal of amorphous and crystalline Fe oxides using oxalate and dithionite, respectively. We found that fine colloidal P was present in two dominant sizes: (i) in associations of organic matter and amorphous Fe (Al) oxides in nanoparticles <20 nm, and (ii) in aggregates of fine clay, organic matter and Fe oxides (more crystalline Fe oxides) with a mean diameter of 170 to 225 nm. Solution 31 P‐nuclear magnetic resonance spectra indicated that the organically bound P predominantly comprised orthophosphate‐monoesters. Approximately 65% of P in the WDFC was liberated after the removal of Fe oxides (especially amorphous Fe oxides). The remaining P was bound to larger‐sized WDFC particles and Fe bearing phyllosilicate minerals. Intriguingly, the removal of Fe by dithionite resulted in a disaggregation of the nanoparticles, evident in higher portions of organically bound P in the <20 nm nanoparticle fraction, and a widening of size distribution pattern in larger‐sized WDFC fraction. We conclude that the crystalline Fe oxides contributed to soil P sequestration by (i) acting as cementing agents contributing to soil fine colloid aggregation, and (ii) binding not only inorganic but also organic P in larger soil WDFC particles. Core Ideas: Improved quantification of P bonding forms in soil nanoparticles and their aggregates. Most P in water dispersible fine colloids is associated with (amorphous) Fe oxides. Crystalline Fe oxides contribute to soil P sequestration. Crystalline Fe oxides act as cementing agents of aggregation for soil fine colloids. Crystalline Fe oxides bind not only inorganic but also organic P in larger soil colloid particles.